Tehran Megacity analysed using Population and Climate change - Arbabi, Azadeh; Arzjani, Zahra; Khaledi, Shahriar; Sabri, Meysam (International Journal of Bio-resource and Stress Management, 2023)
The present paper is an attempt to consider some positive and negative aspects in regard to Tehran’s physical and human environments. It is located in vicinity to historical town Rey. Rapid urbanization of this capital city was started since more than 1000 years ago. Unprecedented population load (11 million in 2007) distributed over 650 km2 is responsible for affecting its micro-climates. These phenomenal changes seem to favor the effect of Alborz, Dasht-e-Kavir and west winds in Tehran as well as the vegetation cover, specifically the urban green belts. The main purpose of this paper is to show the geographical and historical specifications of Tehran as a populated and polluted megacity in the Middle East Asia.